The effect of carbon contamination and argon ion sputtering on the work function of chlorinated indium tin oxide - Whitcher, T.J.; Yeoh, K.H.; Chua, C.L.; Woon, Kai Lin; Chanlek, N.; Nakajima, H.; Saisopa, T.; Songsiriritthigul, P. (Elsevier, 2014)
The work function of indium tin oxide (ITO) was increased by treating ITO with dichlorobenzene with UV light. Carbon contamination of the Cl-ITO was measured using X-ray Photoelectron Spectroscopy (XPS) and argon ion sputtering was used to remove the carbon from the surface. It was found that the carbon contamination from residual dichlorobenzene significantly lowered the work function of the ITO and after argon ion sputtering the work function increased to 5.8 eV. It was found that chlorination of ITO occurs after more than 6 min of UV exposure. Further sputtering of ITO resulted in the removal of the functionalized chlorine, the introduction of argon ion contaminants on the ITO decreases its work function.